2015
DOI: 10.3126/kumj.v12i4.13728
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Hypertension Among Male Police Personnel in Urban Puducherry, India

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
34
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 14 publications
13
34
1
2
Order By: Relevance
“…The prevalence of hypertension in this population was 56.86%, and 43.13% of officers were newly diagnosed. A waist circumference > 90 cm was associated with a higher prevalence of hypertension among police personnel [16]. …”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of hypertension in this population was 56.86%, and 43.13% of officers were newly diagnosed. A waist circumference > 90 cm was associated with a higher prevalence of hypertension among police personnel [16]. …”
Section: Introductionmentioning
confidence: 99%
“…Age, BMI and all correlated with hypertension with obesity class two being the strongest correlation with SBP and DBP followed by BMI. Other studies have also reported that BMI is positively and significantly associated with blood pressures across populations in diverse geographical settings (Levy et al, 2009;Abougalambou and Abougalambou, 2013;Ganesh, Naresh and Bammigatti, 2014). This shows that there is a direct relationship between obesity and hypertension.…”
Section: Discussionmentioning
confidence: 63%
“…The nding is consistent with results of previous studies which reported that aging was associated with increased prevalence of hypertension. 21,31 Age has been recognized as a nonmodi able risk factor attributing to increased cardiovascular risk such as hypertension, 32,33 an assertion supported by studies among adults in Kenya 34 and occupational groups in India 35,36 Potential reasons for this could be changes in the blood vessels causing arterial stiffness, decreased elasticity and vascular resistance which occurs with increasing age. 37,38 The study found that those that are single are two and half times more likely to have hypertension compared to those that are married.…”
Section: Resultsmentioning
confidence: 99%